1984
DOI: 10.1002/jbm.820180403
|View full text |Cite
|
Sign up to set email alerts
|

Applications and failure modes of percutaneous devices: A review

Abstract: Percutaneous devices (PD) are designed to serve a variety of clinical and biomedical research purposes. Characteristically they are objects that permanently penetrate through a defect in the skin. The histological aspects of the implant skin interfacial reactions are reviewed in this article. A short description is presented of common applications of PDs. The five presently identified interfacial failure modes are described histologically with the aid of schematic drawings. These failure modes are marsupializa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
176
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(179 citation statements)
references
References 3 publications
2
176
1
Order By: Relevance
“…[1][2][3] Infection and epithelial growth are two of the principal causes of the failure of percutaneous implants. 1,[3][4][5][6][7][8][9] A biosynthetic soft tissue seal can act as a barrier against epithelial downgrowth and bacterial invasion on subepithelial connective tissues and the implant interface. 1,10,11 The fibroblast plays an important role in the formation of a biologic seal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Infection and epithelial growth are two of the principal causes of the failure of percutaneous implants. 1,[3][4][5][6][7][8][9] A biosynthetic soft tissue seal can act as a barrier against epithelial downgrowth and bacterial invasion on subepithelial connective tissues and the implant interface. 1,10,11 The fibroblast plays an important role in the formation of a biologic seal.…”
Section: Introductionmentioning
confidence: 99%
“…1,[3][4][5][6][7][8][9] A biosynthetic soft tissue seal can act as a barrier against epithelial downgrowth and bacterial invasion on subepithelial connective tissues and the implant interface. 1,10,11 The fibroblast plays an important role in the formation of a biologic seal. The biologic seal of skin is provided by both the epidermis and the dermis, which mainly consist of fibroblasts that produce extracellular matrix (ECM) and various essential components of connective tissues, including glycosaminoglycans and c ollagen in fibrous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…9 Surface topography may also be used to modify epithelial cellular and tissue responses at or near an implant. 10 It has been shown that modification of the microtopography of titanium implants can inhibit the downgrowth of skin epithelial tissue, as 10-m grooves 6,7 and 19-30-m grooves and pits 8 were sufficient to limit epithelial downgrowth and promote connective tissue integration at the implant interface.…”
Section: Introductionmentioning
confidence: 99%
“…The implant-tissue interface where the prosthesis penetrates the skin is prone to inflammation, which can lead to implant failure [24]. To avoid inflammation, different implant designs and coatings were developed and tested in biocompatibility studies in animal models [19,20,24].…”
Section: Introductionmentioning
confidence: 99%
“…The implant-tissue interface where the prosthesis penetrates the skin is prone to inflammation, which can lead to implant failure [24]. To avoid inflammation, different implant designs and coatings were developed and tested in biocompatibility studies in animal models [19,20,24]. Morphological features such as epithelial downgrowth and the inflammatory response were analyzed in histological images obtained from tissue sections [6].…”
Section: Introductionmentioning
confidence: 99%